2012
DOI: 10.1074/jbc.m111.275990
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Requirement Factor A1 (HTRA1) Gene Regulates Angiogenesis through Transforming Growth Factor-β Family Member Growth Differentiation Factor 6

Abstract: Background: Genetic variants of high temperature requirement factor A1 (HTRA1) associate with AMD risk. Results: Growth differentiation factor 6 (GDF6) gene polymorphism significantly associated with AMD. HTRA1 knock-out mice display reduced blood vessel in retina and up-regulation of GDF6. Conclusion: HTRA1 regulates angiogenesis via TGF-␤ signaling by GDF6, a novel disease gene. Significance: This novel pathway of HTRA1 in regulation of vascularization is critical for understanding AMD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 30 publications
0
81
0
Order By: Relevance
“…For example, components, such as collagen VI and TINAGL1, were enriched in coculture and glomerular ECM, whereas the expression of other components was reduced compared with monoculture ECM. Interestingly, proteins associated with vascular development, such as CYR61 23 and HRTA1, 26 were downregulated in coculture ECM compared with GEnC ECM. This finding suggests that paracrine factors may influence cell differentiation and fate.…”
Section: Iv) Ecm Deposition Between Cells Was Quantified By Measurinmentioning
confidence: 98%
“…For example, components, such as collagen VI and TINAGL1, were enriched in coculture and glomerular ECM, whereas the expression of other components was reduced compared with monoculture ECM. Interestingly, proteins associated with vascular development, such as CYR61 23 and HRTA1, 26 were downregulated in coculture ECM compared with GEnC ECM. This finding suggests that paracrine factors may influence cell differentiation and fate.…”
Section: Iv) Ecm Deposition Between Cells Was Quantified By Measurinmentioning
confidence: 98%
“…Several cellular and molecular studies have suggested that HtrA1 serves as a key player in regulating various cellular processes through cleavage of and/or binding to pivotal factors that participate in cell proliferation, migration, and fate (8,9). Moreover, dysregulation of HtrA1 expression or its serine protease activity has been implicated in the pathogenesis of important diseases, such as cancer (1,(6)(7)(8)23), arthritis (19), age-related macular degeneration (AMD) (11,14,27,46,48), and neuropathological disorders (18,22,41). The physiological functions of HtrA1 in vivo, however, remain largely unknown.…”
mentioning
confidence: 99%
“…Immunohistochemistry-Eyes from wild type, HtrA1 knockout, and HtrA1 transgenic mice (12,16,23) were resected and immersed in a fixative containing 4% paraformaldehyde overnight at 4°C. The eyes were embedded in OCT compound and frozen on dry ice.…”
Section: Methodsmentioning
confidence: 99%
“…HTRA1 belongs to the HTRA serine protease family, which is highly conserved from microorganisms to multicellular organisms, including humans (11). Several cellular and molecular studies have suggested that HTRA1 plays a key role in regulating various cellular processes via the cleavage and/or binding of pivotal factors that participate in cell proliferation, migration, and cell fate (12)(13)(14)(15). Recently, up-regulation of human HTRA1 expression in the mouse retinal pigment epithelium (RPE) was shown to induce a branching network of choroidal vessels and polypoidal lesions and severe degeneration of the elastic lamina and tunica media of the choroidal vessels, similar to that observed in AMD and PCV patients (16,17).…”
mentioning
confidence: 99%